Service Performance Measurement Using the Supply Chain Operation Reference Model in The Events and Travel Industry - Wurjaningrum, Febriana; Adienya, Gigih (Universitas Airlangga, 2024)
Objective: This study aims to measure the performance of supply chain services using the Supply Chain Operation Reference (SCOR) Version 11.0 model in the events and travel industry. Design/Methods/Approach: The Supply Chain Operation Reference (SCOR) version 11.0 framework was employed to measure the performance of supply chain services. The performance indicators were assigned weights using the Analytical Hierarchy Process in Expert Choice Software. The performance achievements were marked using the traffic light system method, and an Action Plan was suggested for the company to improve its performance. Findings: The present study found 17 performance indicators consisting of 4 Plan performance attributes, 5 Source performance attributes, 3 Make performance attributes, 2 Deliver performance attributes, 2 Return performance attributes, and 1 Enable performance attribute. The weighting of each indicator resulted in the weight values for each activity from highest to lowest order, namely, Plan (0.317), Enable (0.297), Deliver (0.225), Source (0.95), Make (0.44), and Return (0.22). The performance measurement using a scoring system with the